Synthesis and field experiments of the female sex pheromone of sweet potato weevil, Cylas formicarius - Le Van Dung; Nguyen Cong Hao; Nguyen Thanh Danh; Ngo Le Ngoc Luong; Nguyen Thuy Duong; Nguyen Thi My Thao; Dang Chi Hien (Vietnam Journal of Science and Technology, 2023)
Abstract. (Z)-3-dodecen-1-yl (E)-2-butenoate (1) identified as the sex pheromone of sweet potato weevil, Cylas formicarius Fabricius, had been synthesized successfully from 3-butyn-1-ol and 1‑bromooctane as the starting materials. The overall yield via four steps was 60% calculated on 3-butyn-1-ol. The primary step of the scheme was the stereoselective reduction reaction for alkyne cis-hydrogenation without using molecular hydrogen by Pd2(dba)3-catalyzed. And, this reaction was carried out efficiently with KOH/DMF as the hydrogen source. Next, the field trapping experiments were conducted from February to June 2021 at Tien Thuy ward - Chau Thanh district (Ben Tre province) to develop a simple, easy to construct, cost‐effective, and efficient sex pheromone‐baited trap. Main experiments have given positive results such as the relative to sweet-potato foliage, the trap designs, doses of pheromone lure from 0.1 mg to 0.8 mg, and the effect of lure traps with a dose of 0.4 mg. These values can use well to control the dosage of pheromone in field experiments. Keywords: (Z)-3-dodecen-1-yl (E)-2-butenoate, Cylas formicarius Fabricius, Pd2(dba)3/KOH/DMF, 1-decyne, 1-bromooctane, 3-butyn-1-ol, (Z)-configuration, the average number of captured individuals, sweet potato weevil.